UJI AKTIVITAS ANTIBAKTERI EKSTRAK ALGA Halimeda opuntia DARI PERAIRAN DESA POOPOH KABUPATEN MINAHASA - Bryan Andrew Tikonuwu; Defny Silvia Wewengkang; Erladys Rumondor (PHARMACON, 2024)
Halimeda opuntia is a genus of seaweed from the Chlorophyta division that contains bioactive compounds that can be utilized in various fields, especially in medicine. This study was conducted with the aim of determining the antibacterial activity of Halimeda opuntia algae extracts obtained from coastal waters of Poopoh Village, Tombariri District, Minahasa Regency against Pseudomonas aeruginosa and Staphylococcus aureus bacteria. Samples were extracted by maceration method using 95% ethanol solvent. Antibacterial activity testing was conducted using the Kirby and Bauer Disc Diffusion method. The results showed that the average diameter of the inhibition zone against Pseudomonas aeruginosa test bacteria was 6.83 mm and for Staphylococcus aureus test bacteria was 8.58 mm, the inhibition zone that arose against these two bacteria was included in the medium inhibition category. Through this study, it can be concluded that ethanol extract has antibacterial activity against test bacteria, especially on Staphylococcus aureus bacteria. Keywords: Algae, Halimeda opuntia, antibacterial activity, Pseudomonas aeruginosa, Staphylococcus aureus